2019
DOI: 10.1105/tpc.19.00707
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Bacteria Target Plant Plasmodesmata to Colonize and Invade Surrounding Tissues

Abstract: A hallmark of multicellular organisms is their ability to maintain physiological homeostasis by communicating among cells, tissues, and organs. In plants, intercellular communication is largely dependent on plasmodesmata (PD), which are membrane-lined channels connecting adjacent plant cells. Upon immune stimulation, plants close PD as part of their immune responses. Here, we show that the bacterial pathogen Pseudomonas syringae deploys an effector protein, HopO1-1, that modulates PD function. HopO1-1 is requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 62 publications
0
62
0
Order By: Relevance
“…PLASMODESMATA-LOCATED PROTEIN 5 (PDLP5) RLP Arabidopsis thaliana AT1G70690 Biotic stress [15,21,77,78].…”
Section: Plasmodesmata-located Protein 3 (Pdlp3) Rlpmentioning
confidence: 99%
“…PLASMODESMATA-LOCATED PROTEIN 5 (PDLP5) RLP Arabidopsis thaliana AT1G70690 Biotic stress [15,21,77,78].…”
Section: Plasmodesmata-located Protein 3 (Pdlp3) Rlpmentioning
confidence: 99%
“…The largest molecules can traffic through the cytoplasmic sleeve is known as the size exclusion limit (Kim and Zambryski, 2005). Soluble green fluorescent proteins (1×sGFP; 27 kDa) can freely move between plant cells through PD, whereas the movement of 2×sGFP (54 kDa) and 3×sGFP (71 kDa) are largely inhibited between Arabidopsis cells (Kim et al, 2005;Aung et al, 2020). Among different regulators, callose plays the most prominent role in regulating the PD function.…”
Section: Introductionmentioning
confidence: 99%
“…But, apparently, pathogenic viruses and fungi are not the only ones who know how to modulate PD for spreading virulence signals between cells. Aung et al (2020) demonstrate, in a groundbreaking study, that pathogenic bacteria have also found a way.…”
mentioning
confidence: 96%
“…Scale bars 5 50 mm. (Reprinted from Aung et al [2020], Figure 4A.) [OPEN] Articles can be viewed without a subscription.…”
mentioning
confidence: 99%
See 1 more Smart Citation